Dextromethorphan Analgesia in a Human Experimental Model of Hyperalgesia. (August 2019) - Martin, E.; Narjoz, C.; Decleves, X.; Labat, L.; Lambert, C.; Loriot, M.-A.; Ducheix, G.; Dualé, C.; Pereira, B.; Pickering, G.
Editor's Perspective: What We Already Know about This Topic: Neuropathic pain, which presents abnormal pain manifestations including allodynia and hyperalgesia, is associated with central sensitization involving N -methyl-D-aspartate receptors In the freeze-injury hyperalgesia model, a cold burn leads to development of both primary hyperalgesia and secondary hyperalgesia, which develops away from the site of injury without apparent tissue modification, and is associated with central sensitization and activation of N -methyl-D-aspartate receptors in the spinal cord Dextromethorphan, which is an N -methyl-D-aspartate receptor antagonist, is antihyperalgesic in preclinical pain models What This Article Tells Us That Is New: Using the freeze-injury pain model in a randomized, double-blind, placebo-controlled crossover trial of 30-mg doses of oral dextromethorphan in 20 male volunteers, dextromethorphan was antihyperalgesic and reversed peripheral and central neuronal sensitization Because dextromethorphan had no intrinsic antinociceptive effect in acute pain on healthy skin, N -methyl-D-aspartate receptors may need to be sensitized by pain for dextromethorphan to be effective Background: Central pain sensitization is often refractory to drug treatment. Dextromethorphan, an N -methyl-D-aspartate receptor antagonist, is antihyperalgesic in preclinical pain models. The hypothesis is that dextromethorphan is also antihyperalgesic in humans. Methods: This randomized, double-blind, placebo-controlled, crossover study explores the antihyperalgesic effect of single and repeated 30-mg dose of oral dextromethorphan in 20 volunteers, using the freeze-injury pain model. This model leads to development of primary and secondary hyperalgesia, which develops away from the site of injury and is associated with central sensitization and activation of N -methyl-D-aspartate receptor in the spinal cord. The primary outcome was antihyperalgesia calculated with the area under the curve of the percentage change in mechanical pain threshold (electronic von Frey) on the area of secondary hyperalgesia. The secondary outcomes were mechanical pain threshold on the area of primary hyperalgesia and cognitive (reaction time) effect. Results: Single 30-mg results are reported. Antihyperalgesia (% · min) is significantly higher on the area of secondary hyperalgesia with dextromethorphan than placebo (median [interquartile range]: 3, 029 [746; 6, 195] vs . 710 [–3, 248; 4, 439], P = 0.009, Hedge's g = 0.8, 95% CI [0.1; 1.4]). On primary hyperalgesia area, mechanical pain threshold 2 h after drug intake is significantly higher with dextromethorphan ( P = 0.011, Hedge's g = 0.63, 95% CI [0.01; 1.25]). No difference in antinociception is observed after thermal painful stimuli on healthy skin between groups. Reaction time (ms) is shorter with placebo than with dextromethorphan (median [interquartile range]: 21.6 [–37.4; 0.1] vs . –1.2 [–24.3; 15.4], P = 0.015, Hedge's g = 0.75, 95% CI [0.12; 1.39]). Nonserious adverse events occurrence (15%, 3 of 20 volunteers) was similar in both groups. Conclusions: This study shows that low-dose (30-mg) dextromethorphan is antihyperalgesic in humans on the areas of primary and secondary hyperalgesia and reverses peripheral and central neuronal sensitization. Because dextromethorphan had no intrinsic antinociceptive effect in acute pain on healthy skin, N -methyl-D-aspartate receptor may need to be sensitized by pain for dextromethorphan to be effective. Abstract : Using the freeze-injury pain model in a randomized, double-blind, placebo-controlled crossover trial of 30-mg doses of oral dextromethorphan in 20 male volunteers, dextromethorphan was antihyperalgesic and reversed peripheral and central neuronal sensitization. Because dextromethorphan had no intrinsic antinociceptive effect in acute pain on healthy skin, N-methyl-d-aspartate receptors may need to be sensitized by pain for dextromethorphan to be effective.Supplemental Digital Content is available in the text.